The influence of halogen-mediated interactions on halogen abstraction reactions by formyl radicals - Miranda, Matias Orlando (2025)
This article reports a theoretical study on the halogen exchange reactions YX + CHO → Y + XCHO (with Y = F, Cl, Br; X = Cl, Br, I) carried out at a high level of accuracy using coupled-cluster based methodologies including CCSD(T)-F12, CCSD(T)/CBS and CCSDT(Q)Λ. Most of the reactions are exothermic at room temperature, with the exception of the reactions FI + CHO → F + ICHO and ClI + CHO → Cl + ICHO. Exothermicity follows two concurrent trends established by the strength of the bonds being cleaved and formed: Y = F < Cl < Br (X–Y bond strength) and X = Cl > Br > I (C–X bond strength). Regarding the topology of the potential energy surfaces, we find that at the CCSD level of theory only some processes present the expected reaction profile: a pre-reactive complex (preRC) followed by a transition state (TS) and a post-reactive complex (postRC). However, when triple excitations are taken into account, all reactions become barrierless with no preRC/TS along the reaction profile. We propose that halogen-mediated interactions through the σ-hole, which represent the driving force in the early stages of the title reactions, are responsible for the absence of a tight transition state. We suggest that the strength of these interactions formed during these processes triggers the onset of the halogen atom exchange, before the preRC is formed. Therefore, this study aims to show the relevant role of halogen-mediated interactions in the mechanism of reactions in which a halogen atom is abstracted by the formyl radical (CHO).